Reassessing Creditor-Initiated Debt Restructuring in Indonesia through the Islamic Law Concept of Taʿassur - Muhammad Fitratallah Dahlan; Dewi Mayaningsih; Beny Saputra; Muhammad Aswan; Etty Mulyati (Al-Muamalat, 2026)
This study aims to examine Indonesia’s Suspension of Debt Payment Obligations (PKPU) through the Islamic legal concept of taʿassur (financial distress), focusing on the operation of the current framework as a genuine distress-based restructuring mechanism or creditor-driven outcomes. Even though existing studies have analyzed PKPU from doctrinal and procedural perspectives, limited attention has been given to the evaluation through an integrated Islamic insolvency framework, particularly in relation to debtor capacity and proportionality. A normative juridical method is adopted with statutory, conceptual, and comparative approaches. Furthermore, legislation, selected commercial court decisions, and classical Islamic jurisprudence are analyzed using qualitative doctrinal reasoning. The results show that the absence of a substantive financial-distress test and limited judicial scrutiny permit creditor-initiated PKPU proceedings to contribute to inefficient liquidation, even though Article 222(1) sets out basic eligibility requirements. Insolvency mechanisms should incorporate proportionality, feasibility, and debtor-capacity assessment by applying taʿassur as a normative evaluative framework. This study contributes to insolvency law theory by operationalizing Islamic jurisprudential principles into modern restructuring standards and offers policy implications, including the need for distress-based entry criteria, enhanced judicial oversight, and proportionality-based evaluation of creditor decisions, to support a more balanced and sustainable regime in Indonesia.